Paciente de sexo masculino de 14 años de edad con leucemia mieloide crónica - Ibarra Ochoa, Darwin Julio (2018)
Chronic myeloid leukemia (CML) is a chronic myeloproliferative syndrome of a clonal nature, originated in the mother cell, which results in an excessive number of myeloid cells in all stages of maturation. It was the first malignant disease in which an acquired genetic abnormality was demonstrated and is currently the best studied molecular model of leukemia. In the CML, the chromosomal translocation t (9; 22) (q34; q11) is expressed, which gives rise to the formation of the Philadelphia chromosome (Ph). Because of this translocation 2 new hybrid genes are produced: BCR-ABL on chromosome 22q- or Ph chromosome and reciprocal gene ABL-BCR on chromosome derivative 9q +, which, although transcriptionally active, does not seem to play any functional activity in the disease. Currently, the identification of minimal residual disease by molecular methods is of vital importance for the accurate assessment of the disease's evolutionary status.